Challenges and Factors affecting the implementation of e-Government in Iraq - Qader, Nooruldeen Nasih; Kheder, Mohammed Qader (Journal of University of Human Development, 2016)
e-Government refers to the use of Information Technology by the government agencies, namely, the Internet, Mobile Computing and Wide Area Network which have the ability to transfer relations with businesses, citizens, other governments and the other arms of the government. Therefore, the main facilities of the e-Government is to provision of relevant government information in electronic form to the citizens in a timely manner, empowerment of the people through access to information without the administration, make the best delivery to citizens, enhanced productivity and reduce cost or saving cost in doing business with suppliers and customers of government and contribution in public policy decision making. The primary objective of this paper is to review the available and up to date literature about e-Government implementation stages, its benefits and challenges. Depending on literature, the paper reviews a number of relevant issues regarding Iraqi e-Government, namely, e-Government definition, implementation stages, ’e-readiness’, the benefits of e-Government implementation and it focuses on the challenges of Iraqi e-Government implementation.